Gatekeeping or Provider Choice for Sustainable Health Systems? A Literature Review on Their Impact on Efficiency, Access, and Quality of Services - Christos Ntais; Nikolaos Kontodimopoulos; Michael A. Talias (Journal of Market Access & Health Policy)
As early as 1978, the World Health Organization set primary healthcare as the basis on which health systems should be built worldwide. However, the health systems of the different countries show considerable variations in terms of the implementation of gatekeeping from primary to secondary healthcare and direct access to specialists and hospital care. This literature review attempts to present the gatekeeping system with references to the UK, Sweden, the Netherlands, and Germany compared to the situation in Greece, where no gatekeeping system exists. Particular emphasis is placed on the impact of gatekeeping on the healthcare system’s efficiency, equity of access, and the quality of the services provided. Evidence on the effects of gatekeeping is conflicting or limited by the low internal validity. Making the right gatekeeping implementation decisions is difficult in the absence of data. High-quality research studies on health outcomes, clinical efficacy, cost-effectiveness, quality of life, healthcare quality, utilisation of healthcare services, the burden in the healthcare system, and the opinions of patients, physicians, and policymakers are all necessary for developing policy.